Synthesis, and characterization of metal-organic frameworks -177 for static and dynamic adsorption behavior of CO2 and CH4 - Ullah, S. (Elsevier B.V., 2019)
In this work, a microporous metal organic framework (MOF-177) was synthesized and characterized to investigate the static and dynamic adsorption behavior of CO2 and CH4. The synthesized MOF-177 was found to be six-dimensional shaped channels with an average pore diameter of 1.18 nm. The characterization of synthesized MOF-177 involves the FESEM, powder XRD, FT-IR, TGA/DTG, and BET with nitrogen adsorption. The FESEM images disclosed the distinct crystals with needles type geometrical shape containing large pore with diameter in the range of 20.15 Ã . The surface area of MOF-177 was found to be 1721 m2/g with CO2 adsorption capacity of 1.03 mmol/g and CO2/CH4 equilibrium selectivity of 3.21 at ambient conditions i.e. 1 atm and 25 Â°C. MOF-177 found to be in remarkable regeneration ability by sustaining its CO2 adsorption capacity over several adsorption-desorption cycles. Dynamic separation of binary mixture with compositions (CO2:CH4 30:70 and CO2:CH4 70:30) through a fixed bed column revealed that the CH4 pass through the MOF-177 faster than CO2 indicating the higher selectivity for CO2 compared to CH4. Finally, MOF-177 still hold great promise in CO2 separation from natural gas provided it is protected from moisture. Â© 2019 Elsevier Inc.